Synthesis and characterization of polycrystalline Mo2BC ceramic. Issue 10 (August 2021) - Wang, Shuai; Pang, Xianjuan; Zhang, Zhiyuan; Chang, Baolin; Yang, Jun; Song, Chenfei; Du, Sanming; Zhang, Yongzhen
Highlights: Polycrystalline Mo2 BC ceramic bulks were successfully prepared from elemental powders by SPS route. The synthesized temperature of Mo2 BC ceramic was confirmed to be as low as 1300 ºC. The lattice parameters of as-prepared Mo2 BC ceramic were determined by TEM characterization. For the first time, the mechanical properties of Mo2 BC ceramic bulks were investigated. Abstract: Single-phase polycrystalline Mo2 BC ceramic bulks were synthesized successfully from molybdenum, boron, and graphite powders using the spark plasma sintering method. Herein, it was established that the synthesis temperature of the Mo2 BC ceramic could be as low as 1300 °C. Transmission electron microscopy (TEM) characterization confirmed that the crystal structure of the Mo2 BC ceramic was comparable to that of the MoAlB ceramic. The Vickers hardness of the Mo2 BC ceramic was measured to be 18.1 GPa. Additionally, the compressive strength, flexural strength, and fracture toughness were determined to be 1.74 GPa, 457.72 MPa, and 3.26 MPa· m 1/2, respectively. The Mo2 BC bulk exhibited typical brittle features, in which intergranular and transgranular fractures were the main failure modes.